2013
DOI: 10.2478/bvip-2013-0101
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tumour morphology and structure from U87 and U118 glioma cells cultured on chicken embryo chorioallantoic membrane

Abstract: The objective of this study was the morphological and structural characterisation of glioblastoma multiforme grown in ovo. Glioma cells U87 and U118 were implanted in the chorioallantoic membrane (CAM) of chicken egg. After 10 days of incubation, tumours were resected for further analyses. Culturing two types of glioblastoma tumours from U87 and U118 cell lines has shown a number of differences in their morphology, histology, and ultrastructure. CAM assay proved to be a useful tool for studying glioblastoma gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
0
5
0
2
Order By: Relevance
“…We tested both cell lines because they significantly differed in terms of their morphology, histology, and structure. U87 tumors were almost 3× larger than U118 cells ( Jaworski et al, 2013 ). After the xenograft tumors had grown for 14 days, we divided the mice into two groups.…”
Section: Resultsmentioning
confidence: 89%
“…We tested both cell lines because they significantly differed in terms of their morphology, histology, and structure. U87 tumors were almost 3× larger than U118 cells ( Jaworski et al, 2013 ). After the xenograft tumors had grown for 14 days, we divided the mice into two groups.…”
Section: Resultsmentioning
confidence: 89%
“…As a consequence, the nature of the interactions of biological molecules and/or cells with pG is likely to depend on the site of interaction: the surface or edges. Previous findings indicated that glioblastoma cells had a strong affinity for, and adhered to, the surface of pG flakes, rather than the edges [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These lines are characterized by different phenotypes and the activity of genes involved in regulation of the cell cycle. 16 The objectives of this study are to measure the toxicity of GO and rGO, and the proapoptotic and necrotic activities of graphene in glioma cells and tumors cultured on chorioallantoic membrane.…”
Section: Introductionmentioning
confidence: 99%